2002
DOI: 10.1046/j.1365-2605.2002.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of oestrogen receptor α polymorphisms and androgen receptor CAG trinucleotide repeats with male infertility: a study in 109 Greek infertile men

Abstract: This study was performed to examine the contribution of genetic polymorphism of oestrogen and androgen receptor (AR) genes in male infertility. We have studied in total 173 Greek men, 109 infertile patients and 64 controls (group A). Patients were divided in to three subgroups: group B (n=29) with idiopathic moderate oligospermia, group C (n=42) with azoospermia or idiopathic severe oligospermia and group D (n=38) with azoospermia or oligospermia of various known aetiologies. All patients and controls were gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 18 publications
8
59
1
Order By: Relevance
“…The association between male infertility and ERα and ERβ gene polymorphisms has been explored in several studies that have produced conflicting results (Kukuvitis et al, 2002;Suzuki et al, 2002;Aschim et al, 2005;Lazaros et al, 2010). For example, PvuII and XbaI in ERα have been associated with azoospermia or severe oligozoospermia in 2 reports (Kukuvitis et al, 2002;Suzuki et al, 2002), but others have drawn different conclusions (Tuttelmann et al, 2007;Lazaros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The association between male infertility and ERα and ERβ gene polymorphisms has been explored in several studies that have produced conflicting results (Kukuvitis et al, 2002;Suzuki et al, 2002;Aschim et al, 2005;Lazaros et al, 2010). For example, PvuII and XbaI in ERα have been associated with azoospermia or severe oligozoospermia in 2 reports (Kukuvitis et al, 2002;Suzuki et al, 2002), but others have drawn different conclusions (Tuttelmann et al, 2007;Lazaros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…ESR1 PvuII polymorphism in women was found to affect pregnancy rate following in vitro fertilization (IVF) [7,8], whereas in males ESR1 XbaI polymorphism was suggested to have an effect on azoospermia or idiopathic severe oligospermia [9].…”
Section: Introductionmentioning
confidence: 99%
“…This finding was then corroborated by several studies from a variety of different ethnic populations including Japanese, Caucasian, North American, French, Israeli, Taiwanese and Spanish (Yoshida et al 1999;Dowsing et al 1999;Mifsud et al 2001;Wallerand et al 2001;Patrizio et al 2001;Madgar et al 2002;Pan et al 2002;Casella et al 2003;Asatiani et al 2003;Mengual et al 2003). However, several others, who have investigated Swedish, Belgian, German, Japanese, Danish, Dutch, Indian, Greek, New Zealander, Finish, Hong Kong Chinese and Italian populations were unable to demonstrate an association (Giwercman et al 1998;Legius et al 1999;Hiort et al 1999;Dadze et al 2000;Sasagawa et al 2000Sasagawa et al , 2001Von Eckardstein et al 2001;Yu and Handelsman 2001;Kukuvitis et al 2002;Rajpert-De Meyts et al 2002;Van Golde et al 2002;Thangaraj et al 2002;Dhillon and Husain 2003;Erasmuson et al 2003;Lund et al 2003;Tse et al 2003;Ferlin et al 2004). Interestingly, a study by Komori et al (1999) has suggested that reduction rather than expansion of the CAG repeat (< 16 repeats) is closely related to impaired sperm production in an infertile Japanese population.…”
Section: Discussionmentioning
confidence: 87%
“…decade (Tut et al 1997;Yoshida et al 1999;Dowsing et al 1999;Mifsud et al 2001;Patrizio et al 2001;Wallerand et al 2001;Madgar et al 2002;Pan et al 2002;Asatiani et al 2003;Casella et al 2003;Mengual et al 2003), whereas several others were unable to demonstrate an association (Giwercman et al 1998;Hiort et al 1999;Legius et al 1999;Dadze et al 2000;Sasagawa et al 2000Sasagawa et al , 2001Von Eckardstein et al 2001;Yu and Handelsman 2001;Rajpert-De Meyts et al 2002;Van Golde et al 2002;Thangaraj et al 2002;Kukuvitis et al 2002;Erasmuson et al 2003;Dhillon and Husain 2003;Lund et al 2003;Tse et al 2003;Ferlin et al 2004). Thus, the ethnic background of the population studied may play an important role in the correlation between CAG repeat length and male infertility.…”
mentioning
confidence: 99%